What does the doctor plan to say? Physician-generated plans for advance care planning conversations - Russell, Jessica; Quaack, Karly (Qualitative Health Communication, 2022)
Background: Importance of advance care planning or enabling individuals to make decisions regarding their future care is widely recognized. How physicians plan for or approach such conversations remains understudied. Aim: Physician plans were examined through a multiple goals theoretical framework. Of interest were the goals present within the plans as well as content referenced within each goal category. Method: In an online survey, physicians (n = 45) were provided a hypothetical scenario and asked to design a plan to communicate to the patient about their options for life-sustaining treatment. Providers were asked how they would engage in the conversation and what they would plan to discuss. A content analysis of physician responses was conducted. Results: Findings indicated that plans primarily consisted of task and identity goals. Content of reported plans overwhelmingly involved soliciting patient goals, explaining treatment options, and investigating patient knowledge of the medical condition. Conclusions: The current study addresses the paucity of research around what content providers prioritize and which conversational goals are present. This information affords role clarity for interdisciplinary teams and gives insight to where other team members can contribute to enhance patient outcomes. Reliance on theoretical frameworks offers a systematic build of this research where cross-study connections can be identified.